Comprehensive Analysis and Comparative Evaluation of Bitmap Indexing Methods for Efficient Data Management - Pratima, D.; Moulana, MD. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This review paper provides an in-depth analysis of various bitmap indexing methods and their applications in data management systems. We explore traditional bitmap indexing, compressed bitmap indexing, Roaring bitmaps, and SIMD-based indexing. For each method, we discuss their principles, data structures, algorithms, compression techniques, query performance, memory usage, scalability, and potential applications. We also highlight their strengths, limitations, and comparative analysis based on evaluation metrics. Additionally, we examine current research trends, ongoing efforts, research gaps, and potential future directions in bitmap indexing methods. The insights gained from this review will guide practitioners and researchers in selecting and implementing the most suitable bitmap indexing method for their data management needs.